1997
DOI: 10.1164/ajrccm.156.3.9611067
|View full text |Cite
|
Sign up to set email alerts
|

One Year Treatment with Salmeterol Compared with Beclomethasone in Children with Asthma

Abstract: The aim of this study was to compare the effects of salmeterol and beclomethasone on lung function and symptoms in children with mild to moderate asthma. Sixty-seven children not treated with inhaled corticosteroids were randomized in a double-blind parallel study either to salmeterol 50 micrograms b.i.d. or beclomethasone 200 micrograms b.i.d. After one year, FEV1 significantly increased in the beclomethasone group, whereas in the salmeterol group there was a small reduction. Differences between groups were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
146
0
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(159 citation statements)
references
References 26 publications
6
146
0
6
Order By: Relevance
“…One study of 67 children treated with inhaled BPD 200 g BID for 1 year has found that the growth suppressive effect is progressive, resulting in an increasing deviation of growth rates from normal values over time. 16 However, another study has found the opposite effect. In this study, 50 asthmatic children were treated with inhaled BDP 200 g BID for 30 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of 67 children treated with inhaled BPD 200 g BID for 1 year has found that the growth suppressive effect is progressive, resulting in an increasing deviation of growth rates from normal values over time. 16 However, another study has found the opposite effect. In this study, 50 asthmatic children were treated with inhaled BDP 200 g BID for 30 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…15 The suppression of intermediate-term growth in asthmatic children by inhaled corticosteroids has been documented. 16,17 Although the results do not necessarily apply to children with allergic rhinitis, studies of asthmatic children treated with inhaled corticosteroids have yielded mixed results. One study of 67 children treated with inhaled BPD 200 g BID for 1 year has found that the growth suppressive effect is progressive, resulting in an increasing deviation of growth rates from normal values over time.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized, double-67 children Salmeterol and FEV 1 increase was significantly greater 1997 (16) blind, controlled 6 to 16 years beclomethasone and growth rate was lower (1.4 cm) 54 weeks for 6 weeks in the beclomethasone group than in the salmeterol group (p = 0.001). Simons et al…”
Section: Factors That Influence Systemic Absorptionmentioning
confidence: 97%
“…Neles, esse esquema, de modo regular, tem possibilitado a redução dos sintomas diários de asma bem como da freqüência de asma noturna, a diminuição no consumo de medicação de alívio (ß 2 agonistas de curta duração), melhora da função pulmonar e diminuição das flutuações do pico de fluxo expiratório, redução da HRB específica, o não desenvolvimento de taquifilaxia e a redução dos corticosterói-des 64,65 . Em estudo evolutivo, com duração de quatro meses, avaliou-se a ação do salmeterol e do salbutamol sobre a HRB inespecífica à metacolina.…”
Section: Agentes ß 2 Agonistas De Longa Duraçãounclassified
“…Os pacientes tratados com o corticosteróide inalado apresentaram melhor evolução clínica (redução de sintomas, maior estabilidade do pico de fluxo expirató-rio, redução do consumo de medicação de alívio) e modificações significativas da HRB inespecífica à metacolina. Os tratados com salmeterol manifestaram controle dos parâmetros clínicos e espirométricos, e não houve agravo da HRB, entretanto, tiveram taxa de crescimento em estatura significantemente superior aos que receberam corticosteróides 64,65 .…”
Section: Agentes ß 2 Agonistas De Longa Duraçãounclassified